2007
DOI: 10.1097/01.ta.0000196704.78785.ae
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Controlled Investigation of the Anti-Infective Properties of the Alexis Retractor/Protector of Incision Sites

Abstract: It was suggested that the use of the Alexis wound retractor would protect surgical wounds from contamination by bacteria and thus prevent infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
106
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 11 publications
(5 reference statements)
2
106
0
1
Order By: Relevance
“…The use of the Alexis wound protector has been reported to protect surgical wounds from contamination by bacteria and, consequently, to prevent infection during gastrointestinal surgery. 9 Horiuchi et al 10 reported that the use of the Alexis retractor at incision sites during gastric and colorectal surgery significantly reduced the incidence of wound infections (superficial infections at the sites of surgical incisions) in a randomized controlled study. The same wound protector also significantly reduced the risk of wound complications in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the Alexis wound protector has been reported to protect surgical wounds from contamination by bacteria and, consequently, to prevent infection during gastrointestinal surgery. 9 Horiuchi et al 10 reported that the use of the Alexis retractor at incision sites during gastric and colorectal surgery significantly reduced the incidence of wound infections (superficial infections at the sites of surgical incisions) in a randomized controlled study. The same wound protector also significantly reduced the risk of wound complications in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The Alexis, a polyurethane wound retractor manufactured by Applied Medical, was initially developed to protect against abdominal wounds [10]. It has a flexible cylindrical membrane attached to two semirigid rings on each end.…”
Section: Discussionmentioning
confidence: 99%
“…We think that wound infection refl ects the still active infl ammatory process in complicated diverticulitis and possibly the persistence of bacteria in the pericolic fatty tissue. According to Horiuchi et al,48 the use of a wound retractor can protect surgical wounds from contamination by bacteria and thus prevent infection. Our low rate of wound infection may be attributed to the fact that we always used a wound protector intraoperatively to remove the specimen and perform anastomosis without direct contact with the trocar wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Our low rate of wound infection may be attributed to the fact that we always used a wound protector intraoperatively to remove the specimen and perform anastomosis without direct contact with the trocar wounds. 44,48 Various surgical interventions for complicated diverticulitis include three-stage colostomy, resection, and anastomosis; two-stage Hartmann's procedure; and onestage resection and primary anastomosis. Some trials have demonstrated that complications were more closely associated with the three-stage procedure than with Hartmann's procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation